Guideline for the Development of Teaching and Learning Management in the Disruptive Era of Teachers in Mahachulalongkorngajavidyalaya University - Silatecho, Phra Bounlerd; Phrakruwirunsuttakun, Phrakruwirunsuttakun; Chaisouk, Peerawat (วารสารจิตวิทยาพุทธศาสตร์ประยุกต์เพื่อสังคม, 2022)
The objectives of this research are; 1) to study the state of teaching and learning management of teachers, 2) to study the teaching and learning management in the disruptive era of teachers, and 3) to propose guidelines of teaching and learning management in the disruptive era of teachers in Mahachulalongkornrajavidyalaya University. The mixed research methods were used in the study. The quantitative data were collected by using questionnaire from 159 samples and analyzed by mean and standard deviation. The qualitative data were collected by in-depth interviews with 5 experts and analyzed by content analysis. The results of the study showed that: 1. The state of teaching and learning management of teachers in Mahachulalongkornrajavidyalaya University in 5 aspects was at a high level overall. In apects, the highest level was on learning support activity, followed by media using, measurement and evaluation, teaching and learning operating, and curriculum respectively. 2. The methods of teaching and learning management in the disruptive era of teachers in Mahachulalongkornrajavidyalaya University were as follows: 1) In curriculum, to analyze problems and to design curriculum structure in line with situations and social contexts; 2) In teaching and learning management, to transfer knowledge to students based on the course contents and to apply online teaching and learning for students; 3) In instructional media, to use information technology in teaching and learning; 4) In learning support activity, to arrange variety of activities for new experience encouragement; and 5) In measurement and evaluation, to report accululative scores, summative scores, and grades through online system. 3. The guidelines of teaching and learning management in the disruptive era of teachers in Mahachulalongkornrajavidyalaya University are as follows: to design curriculum structure to encourage thinking skills relevant to vision, aim and requirement characteristics of present society; Teachers use many methods to transfer knowledge to students according to their backgrounds and use online media suitable to learning activities under the teachers’ supervision; and to implement measurement and evaluation relevant to course objectives, to use online examination, to evaluate learning by using examination questions from the test bank, and to communicate and submit learning assignments through online system in order that students can learn new things and apply it in their real life.